Effect of radiographic film quality on SMAW weld defect detection in SA 240 Gr 316L pressure vessels - Khakim, Moh Lukman; H, Rachmad Syarifuddin; S, Hanto; K, Wahyu Dwi; T, Fahniati Sofi (Politeknik Negeri Lhokseumawe, 2025)
This study shows that radiographic film quality significantly affects the accuracy of SMAW weld defect detection in SA 240 Gr 316L pressure vessels. Radiographic evaluations using both the Panoramic and Internal Source Techniques revealed variations in film density, with the Internal Source Technique achieving slightly higher density values (2.78–3.15) than the Panoramic Technique (2.50–2.88). A sensitivity level of 1.66% was achieved, allowing for the identification of slag inclusions (42 mm and 10 mm) and porosity defects (8 mm). Defects exceeding ASME Section V acceptance criteria required re-welding and re-evaluation. Several factors influencing radiographic quality were identified, including radiation source activity, exposure duration, and film processing conditions. Optimizing these parameters is essential for ensuring reliable defect detection and maintaining pressure vessel integrity. Future research could focus on advanced image processing techniques or digital radiography.